Curcumin antifungal and antioxidant activities are increased in the presence of ascorbic acid - Kdudsi Khalil, Omar Arafat [UNESP]; Mascarenhas de Faria Oliveira, Olga Maria [UNESP]; Rebuglio Vellosa, Jose Carlos; de Quadros, Andreza Urba; Dalposso, Loriangela Marceli; Karam, Thaysa Ksiaskiewcz; Mainardes, Rubiana Mara; Khalil, Najeh Maissar (Elsevier B.V., 2012)
The objective of this study was to evaluate the antifungal and antioxidant activities of curcumin, ascorbic acid and the mixture of these two compounds. For the antifungal assay, the minimum inhibitory concentrations (MIC) were determined using Candida strains (ATCC and clinical isolates). Curcumin alone inhibited growth of Candida albicans yeast cells, whereas ascorbic acid did not present effects. However, when the mixture of ascorbic acid and curcumin was assayed to determine the association of the two compounds, the curcumin MIC decreased 5- to 10-fold. In the antioxidant assays, the sum of the alone activities of curcumin and ascorbic acid were lower than the activity of the two-compound mixture. This study highlights the importance of the association between two common antioxidants in foods, to improve the antifungal and antioxidant activities of curcumin (in vitro), and can be applied to Candida spp. infection and diseases associated with oxidative stress. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Curcumin; Ascorbic acid; Antifungal; Antioxidant